2019
DOI: 10.1021/acs.jpca.9b04555
|View full text |Cite
|
Sign up to set email alerts
|

Why Do N-Alkylated Anilides Bend Over? The Factors Dictating the Divergent Conformational Preferences of 2° and 3° N-Aryl Amides

Abstract: The conformational preferences of 28 sterically and electronically diverse N-aryl amides were determined using density functional theory (DFT), using the B3LYP functional and 6-31G­(d) basis set. For each compound, both the cis and trans conformers were optimized, and the difference in ground state energy calculated. For six of the compounds, the potential energy surface was determined as a function of rotation about the N-aryl bond (by 5° increments) for both cis and trans conformers. A natural bond orbital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
(69 reference statements)
1
27
0
Order By: Relevance
“…Analytical HPLC and 1 H NMR analyses of compounds 2-4 demonstrated that they exist as a mixture of atropisomers [24] at ambient temperature. A well-described phenomena for tertiary aromatic amides bearing an ortho substituent wherein the aromatic ring and the amide plane are near perpendicular [25,26]. Hindered rotation about the amide bond results in two conformations that can interconvert slowly on an NMR timescale at ambient temperature and are hence detectable by NMR and characterized by chemical exchange effects in NMR experiments [27][28][29].…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical HPLC and 1 H NMR analyses of compounds 2-4 demonstrated that they exist as a mixture of atropisomers [24] at ambient temperature. A well-described phenomena for tertiary aromatic amides bearing an ortho substituent wherein the aromatic ring and the amide plane are near perpendicular [25,26]. Hindered rotation about the amide bond results in two conformations that can interconvert slowly on an NMR timescale at ambient temperature and are hence detectable by NMR and characterized by chemical exchange effects in NMR experiments [27][28][29].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…tert-Butyl 4-(ethylsulfonyl)-5-fluoro-2-nitrobenzoate (26). Reaction of compound 18 (24.4 g, 87.8 mmol) with tert-butyl acetate (150 mL) and perchloric acid (70%, 3.70 mL, 61.4 mmol), using the same procedure as described for 25, afforded the title compound 26 as pale-yellow crystals (20.5 g, 70%), M.p.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…For all intermediates, a conformational analysis was carried out considering the possibility of a rotation around the amide bond. Following the oxidative addition, the cis structure (shown in Figure ) is more stable than the trans conformer in the case of 5d-II , which agrees with the previous findings for tertiary N -aryl amides . After the coordination of the carbonate ( 5d-III ), the cis structure (shown in Figure ) is destabilized because of increased repulsion between the phenyl ring and the carbonate ion.…”
Section: Resultsmentioning
confidence: 99%
“… Specific hyperconjugative contributions from the methyl groups to the eight conformers in Figure 2 were obtained by deletion of all donor→acceptor interactions involving the methyl groups. Hyperconjugation effects on molecular geometries: following a strategy suggested elsewhere [ 29 , 78 , 79 , 80 , 81 , 82 ], geometry optimizations for the rotations of the methyl groups within the lowest energy structure were carried out by deleting all hyperconjugative interactions involving each methyl group separately and then involving all methyl groups simultaneously. …”
Section: Methodsmentioning
confidence: 99%
“…Hyperconjugation effects on molecular geometries: following a strategy suggested elsewhere [ 29 , 78 , 79 , 80 , 81 , 82 ], geometry optimizations for the rotations of the methyl groups within the lowest energy structure were carried out by deleting all hyperconjugative interactions involving each methyl group separately and then involving all methyl groups simultaneously.…”
Section: Methodsmentioning
confidence: 99%